(untitled) (Journal of Computational Mathematics, 1985)
In this paper, the isoparametric element of 2-degree Lagrange type for second order elliptic P.D.E, with nonhomogeneous Dirichlet boundary value is considered. We prove \|u-u_h\|_1,Ω=O(h^2), which is the same as \|u-u_h\|_1,Ω_h=O(h^2) where Ω and Ω_h in R^2 are the domain of the boundary value problem and isoparametric triangulation domain respectively.